Genetic diversity among kenaf mutants as revealed by Qualitative and Quantitative traits - Al-Mamun, Mohammad; Rafii, Mohd; Oladosu, Yusuff; Misran, Azizah; Berahim, Zulkarami; Khan, Mahmudul Hasan; Arolu, Fatai (Taylor & Francis, 2022)
Understanding the genetic variability using different qualitative and quantitative traits plays a significant role in kenaf breeding program. To achieve this objective, a study was conducted on yield and yield components over two planting seasons to evaluate genetic diversity and heritability among kenaf mutant lines using multivariate analysis to identify superior genotype for future breeding program. Highly significant differences (p ≤ 0.01) was recorded among the qualitative and quantitative traits. Strong to moderately positive phenotypic correlation was observed between dry fiber weights for all the morphological traits except top diameter and days to flowering. The 31 studied genotypes were grouped into six major clusters based on the UPGMA dendrogram. Principal component analysis based on the correlation matrix of 15 quantitative traits showed that the first five components accounted for 85.16% of the total variation of the genotypes. Based on diversity pattern and morphophysiological performance, hybridization of group IV with group VI, or group III, group V and group I could be used to attain high vigor or heterosis with a comparative photo-insensitive variety with high fiber yield. Also, this evaluation could be useful in developing reliable selection criteria for future improvement in kenaf breeding programs.